1990
DOI: 10.1677/joe.0.1270505
|View full text |Cite
|
Sign up to set email alerts
|

Steroid fatty acid esters in adrenals and plasma: effects of ACTH

Abstract: The presence and production of 5-ene-steroid fatty acid esters (SFA) has been previously reported in bovine adrenals. A study was conducted, using a series of chromatographic procedures and radioimmunoassays, to determine the levels of SFA in adrenals from man, cattle, dog, rat and guinea-pig, and to assess, in both rats and guinea-pigs, the effect of ACTH on SFA production by adrenals and their subsequent secretion into the circulation. The effects of ACTH on plasma SFA and non-conjugated steroid levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Recently, Jung et al [83] analyzed intact saturated fatty acid esters of dehydroepiandrosterone and pregnenolone in five women and men by GC-MS. In contrast to previous work, the reported male plasma concentration of a representative pregnenolone fatty acid ester, pregnenolone 3-stearate, was over 100 times higher (99-1800 nmol/l) than the total plasma pregnenolone fatty acid ester concentration as previously analyzed by indirect methods (1-6.5 nmol/l) [2,54,84]. Unfortunately, the plasma concentration of unesterified pregnenolone was not reported [83].…”
Section: Circulating Steroid Fatty Acid Esterscontrasting
confidence: 75%
“…Recently, Jung et al [83] analyzed intact saturated fatty acid esters of dehydroepiandrosterone and pregnenolone in five women and men by GC-MS. In contrast to previous work, the reported male plasma concentration of a representative pregnenolone fatty acid ester, pregnenolone 3-stearate, was over 100 times higher (99-1800 nmol/l) than the total plasma pregnenolone fatty acid ester concentration as previously analyzed by indirect methods (1-6.5 nmol/l) [2,54,84]. Unfortunately, the plasma concentration of unesterified pregnenolone was not reported [83].…”
Section: Circulating Steroid Fatty Acid Esterscontrasting
confidence: 75%
“…These known lipoidal steroid conjugates have been found in several tissues (54,56), and several authors have suggested that C 21 , C 19 , and C 18 steroids linked to fatty acids via hydroxyl functions at positions C-3, C-17, and C-21 are sequestered in tissues in which the unconjugated steroid can be released by the action of intracellular esterases (57). Furthermore, these esters of PREG, DHEA, androst-5-ene-3␤,17␤-diol, and estradiol can be formed in plasma of several mammalian species (58,59). It has also been shown that plasma lipoproteins serve as carriers of PREG and DHEA fatty acid esters because of their very low aqueous solubility (60).…”
Section: Structural Identification: Some Hypothesesmentioning
confidence: 99%
“…Pituitary hormones, by acting on specific target cells, can increase the circulating pregnenolone and progester one content [22] and these stereoids are taken up by the brain [23]. In order to establish whether chloral hydrate, ethanol, and urethane increase the content of brain ste roids by acting directly on brain steroid biosynthesis or indirectly via an increase secretin of pituitary hormone acting on steroidogenic cells we injected chloral hydrate to hypophysectomized or castrated-adrenalectomized rats.…”
Section: Effect O F Anesthetics On Pregnenolone and Progesterone Braimentioning
confidence: 99%